2016
DOI: 10.1002/polb.24251
|View full text |Cite
|
Sign up to set email alerts
|

Small-angle neutron scattering analysis of bottlebrush backbone and side chain flexibility

Abstract: Bottlebrush polymers have densely tethered side chains grafted to a linear polymer backbone, resulting in stretching of both the side chains and backbone. Prior studies have reported that the side chains are only weakly stretched while the backbone is highly elongated. Here, scaling laws for the bottlebrush backbone and side chains are determined through small-angle neutron scattering analysis of a systematic series of poly(lactic acid) bottlebrush polymers synthesized via a "grafting-through" ring-opening pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 53 publications
6
64
0
Order By: Relevance
“…The backbones are drawn in the fully extended limit for ease of visualization, and the side chain conformations and cross-sectional radii are depicted as anticipated by existing theory. 5,[44][45][46] BP-1 was synthesized by first copolymerizing PDMS and endo,exo-norbornenyl dimethylester (dx-DMeE, 1a) in a 1:1 feed ratio. Since r1 = 1.1 and r2 = 0.94, the first block has an ideal random backbone sequence and therefore uniform side chain distribution.…”
Section: Chart 1 Monomer Design For Ring-opening Metathesis Copolymementioning
confidence: 99%
See 1 more Smart Citation
“…The backbones are drawn in the fully extended limit for ease of visualization, and the side chain conformations and cross-sectional radii are depicted as anticipated by existing theory. 5,[44][45][46] BP-1 was synthesized by first copolymerizing PDMS and endo,exo-norbornenyl dimethylester (dx-DMeE, 1a) in a 1:1 feed ratio. Since r1 = 1.1 and r2 = 0.94, the first block has an ideal random backbone sequence and therefore uniform side chain distribution.…”
Section: Chart 1 Monomer Design For Ring-opening Metathesis Copolymementioning
confidence: 99%
“…[39][40][41][42][43] These cylindrical brushes can be modeled as wormlike chains with the same average crosssectional radius (Rc) along the entire backbone. 5,[44][45][46] On the other hand, if the macromonomer and diluent copolymerize at different rates, the resulting gradient sequences are anticipated to template different side chain conformations. Depending on the extent of side chain stretching, Rc varies and tapered, noncylindrical molecular shapes result ( Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…The connection between these predictions and experimental systems remains sparse in the literature, but qualitative trends from both experiments and computer simulations suggest that the overall size and persistence length of bottlebrushes does increase due to the presence of side chains. 7,35,[72][73][74] In particular, both SANS 75 and light scattering and viscosity 76 have shown evidence that p can increase by an order of magnitude as the length of side chains increases. In case of molecules with dendronized side chains (upto third generation), light scattering studies 77,78 have shown a modest increase in p ; the overall conformation appearing more like a semiflexible chain rather than a rigid rod.…”
Section: Introductionmentioning
confidence: 99%
“…Bottlebrush polymers have attracted considerable attention in the last few years due to their unique molecular structural features, and these materials have inspired the design of novel applications as rheological property modifiers, 1 pressure sensors, 2 photonic bandgap materials, [3][4][5] pH-sensitive probes, 6 supersoft elastomers, 7,8 nanostructured morphologies, [9][10][11][12][13] and drug delivery agents. 14 Despite advances in polymer synthesis techniques for creating branched molecules with precise control of molecular architecture, [15][16][17][18][19] as well as, experimental 7,12,[19][20][21][22][23][24][25][26][27] and simulation, 11,13,[28][29][30] methods to establish structure property relationships between the bottlebrush polymer architecture, a general understanding of the physical properties of these materials remains largely unexplored. Part of the scientific challenge here is that direct experimental measurements of conformational properties in the melt state are difficult and experimental observations of these properties are often performed in solution rather than in the melt state.…”
Section: Introductionmentioning
confidence: 99%